Fasting Leptin Is a Metabolic Determinant of Food Reward in Overweight and Obese Individuals during Chronic Aerobic Exercise Training. (10th March 2014) - Hopkins, Mark; Gibbons, Catherine; Caudwell, Phillipa; Webb, Dominic-Luc; Hellström, Per M.; Näslund, Erik; Blundell, John E.; Finlayson, Graham
Abstract : Changes in food reward have been implicated in exercise-induced compensatory eating behaviour. However, the underlying mechanisms of food reward, and the physiological correlates of exercise-induced changes in food reward, are unknown. Methods. Forty-six overweight and obese individuals completed 12 weeks of aerobic exercise. Body composition, food intake, and fasting metabolic-related hormones were measured at baseline, week six, and postintervention. On separate days, the reward value of high-and-low-fat food (explicit liking and implicit wanting) was also assessed at baseline, week six, and postintervention. Results. Following the intervention, FM, FFM, and V O 2 peak improved significantly, while fasting leptin decreased. However, food intake or reward did not change significantly. Cross-sectional analyses indicated that FM (P = 0.022 ) and FFM (P = 0.046 ) were associated with explicit liking for high-fat food, but implicit wanting was associated with FM only (P = 0.005 ). Fasting leptin was associated with liking (P = 0.023 ) and wanting (P = 0.021 ) for high-fat food. Furthermore, a greater exercise-induced decline in fasting leptin was associated with increased liking (P = 0.018 ). Conclusion. These data indicate that food reward has a number of physiological correlates. In particular, fasting leptin appears to play an active role in mediating food reward during exercise-induced weight loss.